2019
DOI: 10.3390/mca24010028
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Element Method Modeling of Eddy Current Losses in High-Frequency Transformers

Abstract: This paper concerns the modeling of eddy current losses in conductive materials in the vicinity of a high-frequency transformer; more specifically, in two-dimensional problems where a high ratio between the object dimensions and the skin-depth exists. The analysis is performed using the Spectral Element Method (SEM), where high order Legendre–Gauss–Lobatto polynomials are applied to increase the accuracy of the results with respect to the Finite Element Method (FEM). A convergence analysis is performed on a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…p-refinement. This feature is particularly useful for solving high-frequency eddy current problems where a high ratio between the object dimensions and the skin-depth exists [19]. Furthermore, the SEM applies Gaussian quadratures in order to perform numerical integration, whereas divergence operators are evaluated using Lagrangian basis functions.…”
Section: Magneticmentioning
confidence: 99%
See 2 more Smart Citations
“…p-refinement. This feature is particularly useful for solving high-frequency eddy current problems where a high ratio between the object dimensions and the skin-depth exists [19]. Furthermore, the SEM applies Gaussian quadratures in order to perform numerical integration, whereas divergence operators are evaluated using Lagrangian basis functions.…”
Section: Magneticmentioning
confidence: 99%
“…Furthermore, the SEM applies Gaussian quadratures in order to perform numerical integration, whereas divergence operators are evaluated using Lagrangian basis functions. Additional details on the formulation and implementation of the method can be found in [14,15,19,31].…”
Section: Magneticmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM was originally applied to problems occurring in fluid dynamics and meteorology [28]. Over the past decades, the application of the method has spread to a wide variety of linear and non-linear engineering and mathematical problems [29], e.g., wave propagation, structural analysis, astrophysics, financial engineering, and more recently electromagnetic field modeling [27,30], including eddy current problems [16,20,31]. The formulation of the SEM for 2D Cartesian magnetostatic and thermal problems is presented in [27], of which the former has been applied to a linear synchronous actuator in [32].…”
Section: Introductionmentioning
confidence: 99%
“…Another example is observed in [33], where a coupled SEM-FEM approach is applied to investigate magnetoconvection for transformer cooling. In the context of high-frequency axisymmetric WPT systems, in [31], the SEM has been applied for the modeling of the losses that are induced in an electrically conductive and permeable cylinder, which surrounds the domain. The results have demonstrated that, compared to the FEM, the SEM obtains a higher accuracy per degree of freedom (DoF) and lower computation time.…”
Section: Introductionmentioning
confidence: 99%